Spectrum demand prediction ofLTE-Rsystem based on delay difference constraint - Peng LIU; Wei LI; Bin LIU; Tan WANG; Suiyan GENG (Dianxin kexue)
In order to plan and allocate the spectrum resources ofLTE-Rscientifically,it is necessary to make reasonable forecast of total spectrum demand for LTE-R.After deep analysis of ITU-R M.1768 method,a spectrum demand forecasting method based on different delay constraints forLTE-Rsystem was provided.This method defined nine kinds of service categories,nine kinds of service environments,and derived the expression ofLTE-Rsystem traffic.Under different delay constraints condition of different services,the M/G/1 queuing model was used to analyze the spectrum requirements ofLTE-Rsystem preliminarily.The results show that the uplink and downlink spectrum demand of China’sLTE-Rsystem is asymmetric and the possible range is 14~15MHz uplink and 5~6MHz downlink,respectively.If new video traffic in the future is not considered,the current spectrum resources distributed to GSM-R system spectrum can meet the bandwidth requirements ofLTE-Rsystem.In addition,the influence of engineering frequency efficiency ofLTE-Rnetwork and high-bandwidth video traffic onLTE-Rspectrum total bandwidth demand was analyzed.This study provides technical support for the frequency planning of China’s next generation railway mobile communication system.